BRCA1/2 potential founder variants in the Jordanian population: an opportunity for a customized screening panel - Ahmad, Olfat; Sutter, Christian; Hirsch, Steffen; Pfister, Stefan; Schaaf, Christian P. (Hereditary cancer in clinical practice, 2023)
A founder variant is a genetic alteration, that is inherited from a common ancestor together with a surrounding chromosomal segment, and is observed at a high frequency in a defined population. This founder effect occurs as a consequence of long-standing inbreeding of isolated populations. For high-risk cancer predisposition genes, such as BRCA1/2, the identification of founder variants in a certain population could help designing customized cost-effective cancer screening panels. This advantage has been best utilized in designing a customized breast cancer BRCA screening panel for the Ashkenazi Jews (AJ) population, composed of the three BRCA founder variants which account for approximately 90% of identified BRCA alterations. Indeed, the high prevalence of pathogenic BRCA1/2 variants among AJ (~ 2%) has additionally contributed to make population-based screening cost-effective in comparison to family-history-based screening. In Jordan there are multiple demographic characteristics supporting the proposal of a founder effect. A high consanguinity rate of ~ 57% in the nineties of the last century and ~ 30% more recently is a prominent factor, in addition to inbreeding which is often practiced by different sub-populations of the country.